2019
DOI: 10.1007/s10877-019-00291-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-site regional oxygen saturation and capnography monitoring during resuscitation after cardiac arrest in a swine pediatric ventricular fibrillatory arrest model

Abstract: To investigate the use of two-site regional oxygen saturations (rSO 2) and end tidal carbon dioxide (EtCO 2) to assess the effectiveness of resuscitation and return of spontaneous circulation (ROSC). Eight mechanically ventilated juvenile swine underwent 28 ventricular fibrillatory arrests with open cardiac massage. Cardiac massage was administered to achieve target pulmonary blood flow (PBF) as a percentage of pre-cardiac arrest baseline. Non-invasive data, including, EtCO 2 , cerebral rSO 2 (C-rSO 2) and ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Some authors suggested that VCO 2 and VCO 2 /kg were also good predictors of ROSC 17 , 20 , 21 , although these parameters did not demonstrate utility for this purpose in our study. Most of these studies induced a ventricular-fibrillation cardiac arrest.…”
Section: Discussioncontrasting
confidence: 80%
“…Some authors suggested that VCO 2 and VCO 2 /kg were also good predictors of ROSC 17 , 20 , 21 , although these parameters did not demonstrate utility for this purpose in our study. Most of these studies induced a ventricular-fibrillation cardiac arrest.…”
Section: Discussioncontrasting
confidence: 80%
“…Cerebral tissue oxygen saturation during CPR is greater in patients with ROSC than in those without [ 3 – 7 , 11 ]. Furthermore, cerebral tissue oxygen saturation during CPR is correlated with cardiac output [ 16 ]. This may imply that the increase in cardiac output, as generated by high-quality CPR, may increase systemic organ perfusion, systemic oxygenation, pulmonary perfusion, and cerebral tissue oxygen saturation, leading to the achievement of ROSC combined with improved coronary perfusion and oxygenation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Planned secondary analysis was performed on data collected in a previous study that investigated the use of two-site regional oxygen saturations and EtCO 2 to assess the effectiveness of resuscitation and identify ROSC in a swine VF cardiac arrest model. 21 The initial study protocol was approved by The University of Wisconsin Institutional Animal Care and Use Committee, as per the guidelines in the United States Department of Health and Human Services and the National Institutes for Health.…”
Section: Methodsmentioning
confidence: 99%